Prototype Sistem Informasi Data Kependudukan dan Potensi Desa Berbasis Website (Studi Kasus: Desa Tunjung Teja, Kabupaten Serang, Provinsi Banten) - Fadilah, Ila Nurul; Sofian, Erza (LPPM of STIMIK ESQ, 2017)
Tunjung Teja currently does not have information system to manage and documentation for population data and potential data. By the aim of assisting the Tunjung teja in building information system to manage and documentation the demographic data and potential of the village then made a prototype information system of population data and potential village-based website. The method used in make the prototype of village information system is using Scrum method and designed using Unified Modelling Language (UML) modeling language. In this research, the prototype of village-based information system containing village profile, village potency, family card data and poverty data of Tunjung Teja are expected to assist the village in managing data and providing information about Tunjung Teja.